2019
DOI: 10.3389/fped.2019.00326
|View full text |Cite
|
Sign up to set email alerts
|

A Metagenomics Study on Hirschsprung's Disease Associated Enterocolitis: Biodiversity and Gut Microbial Homeostasis Depend on Resection Length and Patient's Clinical History

Abstract: Objectives: Since 2010, several researches demonstrated that microbiota dynamics correlate and can even predispose to Hirschsprung (HSCR) associated enterocolitis (HAEC). This study aims at assessing the structure of the microbiota of HSCR patients in relation to extent of aganglionosis and HAEC status. Methods: All consecutive HSCR patients admitted to Gaslini Institute (Genova, Italy) between May 2012 and November 2014 were enrolled. Institutional review board (IRB) approva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 52 publications
0
16
0
Order By: Relevance
“…Another possible explanation for the observed differences in bacterial taxa in our study compared to others is that we specifically analyzed tissue samples from the surgically resected aganglionic bowel and we identified particular bacterial profiles as possible predictors for postoperative HAEC. In contrast, other studies analyzed fecal samples from the remaining ganglionic bowel of variable lengths at different time points after definitive corrective surgery that could lead to intestinal dysmotility and fecal matter stasis, all variables that have been shown to alter the diversity of the intestinal microbiota [ 17 ]. In addition, the discrepancies between the microbiota profiles from our study and even across other studies could be explained by the heterogenicity of the patient population, ethnicity, geographic location, disease state, antibiotic exposure and age at the time of definitive corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Another possible explanation for the observed differences in bacterial taxa in our study compared to others is that we specifically analyzed tissue samples from the surgically resected aganglionic bowel and we identified particular bacterial profiles as possible predictors for postoperative HAEC. In contrast, other studies analyzed fecal samples from the remaining ganglionic bowel of variable lengths at different time points after definitive corrective surgery that could lead to intestinal dysmotility and fecal matter stasis, all variables that have been shown to alter the diversity of the intestinal microbiota [ 17 ]. In addition, the discrepancies between the microbiota profiles from our study and even across other studies could be explained by the heterogenicity of the patient population, ethnicity, geographic location, disease state, antibiotic exposure and age at the time of definitive corrective surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of HAEC is known to be dysbiosis of the gut microbiota, mucosal barrier dysfunction, change in the gut immune system, and bacterial translocation [19]. A recent study showed that total colonic resections in HD patients, compared with sigmoid resection, changed the composition of intestinal microbiota and reduced microbial diversity [20]. It is, thus, speculated that the longer aganglionic segment impairs the gut micro-environment and induces enteric inflammation of more vulnerable intestinal regions than the shorter aganglionic segment does, even after radical surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, anemia in patients with HD may be associated with altered intestinal microenvironments. A recent study revealed that it lacks a part of probiotics in the intestines of children with HD, the intestinal microecology balance is broken, and the biological barrier provided by the intestinal mucosa is damaged [ 9 ]. The microbes in the colon not only affect the solubility and forms of trace minerals considerably [ 9 ] but also regulate the expression of iron transporter genes.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that it lacks a part of probiotics in the intestines of children with HD, the intestinal microecology balance is broken, and the biological barrier provided by the intestinal mucosa is damaged [ 9 ]. The microbes in the colon not only affect the solubility and forms of trace minerals considerably [ 9 ] but also regulate the expression of iron transporter genes. Therefore, the composition and quantity of the intestinal microbiota affect iron absorption [ 10 ].…”
Section: Discussionmentioning
confidence: 99%